Tracking abortion bans across the country - Mccann, Allison; Walker, Amy Schoenfeld (Periódicos Brasil. Pesquisa Científica, 2024)
Nineteen states ban abortion or restrict the procedure earlier in pregnancy than the standard set by Roe v. Wade, which governed reproductive rights for nearly half a century until the Supreme Court overturned the decision in 2022. In some states, the fight over abortion access is still taking place in courtrooms, where advocates have sued to block bans and restrictions. Other states have moved to expand access to abortion by adopting constitutional amendments or adding legal protections. The New York Times is tracking abortion laws in each state after the Supreme Court’s decision in Dobbs v. Jackson Women’s Health Organization, which ended the constitutional right to an abortion. Where abortion is legal Abortion is broadly legal in 31 states and Washington, D.C. In Wyoming, the procedure remains legal for now as courts determine whether separate laws banning most abortions can take effect. More than half of the states where abortion is legal limit the procedure to around fetal “viability,” the point at which a fetus could survive outside the uterus, or around 24 weeks of pregnancy. This excerpt is a sharing of the original material that can be accessed in full at this link https://www.nytimes.com/interactive/2024/us/abortion-laws-roe-v-wade.html